Association between changes in corrected anion gap and mortality among critically ill patients during ICU stay: a multicenter observational study - Hou, Yanli; Li, Ruohan; Li, Jiamei; Zhang, Jingjing; Ren, Jiajia; Gao, Ya; Jin, Xuting; Luo, Yanni; Wang, Xiaochuang; Wang, Gang (Frontiers in Physiology, 2025)
BackgroundThe research on the impact of dynamic corrected anion gap (cAG) on prognosis is scarce.ObjectiveThis study aimed to investigate the relationship between changes in cAG (ΔcAG) during intensive care unit (ICU) hospitalization and mortality.MethodsIn this multicenter, retrospective cohort study, patients with both initial and final records of serum sodium, potassium, chloride, bicarbonate, and albumin were recruited from the eICU Collaborative Research Database. Two cohorts were included in the study: cohort A (final cAG > initial cAG) and cohort B (final cAG < initial cAG). Multivariable logistic regression was utilized to assess the association between mortality and ΔcAG in each cohort. ΔcAG was calculated as shown as follows: ΔcAG=|final cAG ‐ initial cAG|initial cAG×100%.ResultsAmong the 11,216 enrolled patients, 4,147 (37%) individuals were classified into cohort A, while 7,069 (63%) patients were assigned to cohort B. In cohort A, for every 10% increase in ΔcAG, ICU and hospital mortalities increased by 46.1% (odds ratio: 1.461, 95% confidence interval [1.378, 1.548]) and 55.5% (1.555 [1.467, 1.648]), respectively. Interaction and subgroup analyses demonstrated consistent results among patients with different Acute Physiology and Chronic Health Evaluation Ⅳ (APACHE Ⅳ) scores (≤58 vs. >58), time interval (≤97 h vs. >97 h) and initial cAG (≤16 mEq/L vs. >16 mEq/L). Meanwhile, in cohort B, ICU and hospital mortalities decreased by 31.4% (0.686 [0.619, 0.759]) and 29.4% (0.706 [0.651, 0.764]), respectively, with each 10% increase in ΔcAG, especially among patients with higher APACHE IV scores (>62) and initial cAG (>16 mEq/L). When analyzed categorically, the ΔcAG still exhibited a significant risk gradient across quartiles.ConclusionFurther elevated cAG after ICU admission demonstrates a robust association with an increased mortality risk in critically ill patients. ICU patients with higher APACHE Ⅳ scores or initial cAG may benefit from measures aimed at reducing cAG.